Anaphoras that stop being anaphoras: on the interaction between discourse and morphosyntax - Fábregas, Antonio (Romanica Olomucensia, 2014)
There is a debate about whether the appropriate level to study referential relations between pronominal expressions should be morphosyntactic or discursive. This article explores the issue through a study of some cases where the referential sense of a pronoun does not correspond to its morphosyntactic endowment. It is concluded that morphosyntax is necessary to ban otherwise possible discursive construals, but that - in possible structures - the interpretation received by pronouns is determined by discursive factors
Keywords: anaphoric expressions; pronouns; clitics; discourse; reference shift.